Preparation of SrTiO3 perovskite decorated rGO and electrochemical detection of nitroaromatics. (10th October 2016) - Ahmad, Khursheed; Mohammad, Akbar; Mathur, Pradeep; Mobin, Shaikh M.
Graphical abstract: Present article demonstrates the facile in situ synthesis of reduced graphene oxide-SrTiO3 (rGO-SrTiO3 ) nanocomposite. A binder free sensor was fabricated by coating rGO-SrTiO3 nanocomposite on the surface of glassy carbon electrode. The modified electrode (MGCE ) exhibited good electrocatalytic activity towards different nitroaromatics. Abstract: A perovskite (SrTiO3 ) and reduced graphene oxide (rGO) based nanocomposite (rGO/SrTiO3 ) material has been synthesized i n-situ. The rGO/SrTiO3 nanocomposite was characterized by PXRD, SEM, EDX mapping, TEM and SAED pattern to confirm its purity and morphology. The surface of the glassy carbon electrode (GCE) was modified by coating rGO/SrTiO3 nanocomposite without any binder. This modified electrode GCE-rGO/SrTiO3 (MGCE ) was employed for electrochemical detection of nitro-substituted aromatics such as p -nitrophenol ( p -NP), 2, 4-dinitrophenol (2, 4-DNP), 2, 4-dinitrotoluene (2, 4-DNT) and 2, 4, 6-trinitrophenol (TNP) which shows a rapid electronic communications. TheMGCE exhibited the limit of detection (LOD) of 110 nM, 134 nM, 128 nM, 146 nM, high sensitivity of 193.43 μA μM −1 cm −2, 25.34 μA μM −1 cm −2, 71.66 μA μM −1 cm −2, 13.16 μA μM −1 cm −2 and a linear range between 0.3–0.8, 0.4–0.7, 0.5–0.8, 0.5–0.7 μM for p -NP, 2, 4-DNP, 2, 4-DNT and TNP, respectively. The developed MGCE sensor thus implemented is also advantageous for its low cost, stability, reliability and rendering applications for real system analysis.